Peran Parenting Partnership dalam Meningkatkan Kemandirian Anak Usia 4–5 Tahun melalui Home-Based Learning: Studi Kasus di RA Nurul Huda - Ulya Ainur Rofi’ah; Rifqi Aulia; Widya Fajar Oktaviana (Golden Age and Inclusive Education, 2025)
This study analyzes the effectiveness of home-based learning through a parenting partnership in enhancing the independence of children aged 4-5 years at RA Nurul Huda Semarang. Using a qualitative approach with a case study method, data were collected through interviews, observations, and documentation. The findings indicate a significant improvement in children's independence, such as eating independently (40% to 75%) and dressing themselves (25% to 60%). This success was supported by improved parental communication patterns and consistent positive reinforcement. This study confirms that the collaboration between teachers and parents in home-based learning is effective in fostering children's independence. Children become more confident and self-sufficient in completing daily tasks, demonstrating that proper parental guidance can optimally support their development.